An Analysis of Figurative Language in Adele’s Songs Easy on Me and When We Were Young - Salam, Trisnayanti; Kumayas, Tirza A.; Sabudu, Delli (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The title of this research is " An Analysis of Figurative Language In Adele Songs’ Easy On Me And When We Were Young ". This research aims to describe the types and meaning of figurative language in lyrics of Adele’s Songs. The method used is descriptive qualitative, analysis with a pragmatics approach. The relevant theories that researchers use are figurative language (Rambi & Kumayas 2021:378), theory of types of figurative language in Keraf (2004:136-145). Based on the research results, The figurative language found in “Easy on me” reveals her self-reflection mode as well as vulnerability while navigating through acceptances as well as changes. On the same note “When We Were Young” employs descriptive language full of images and metaphors that express melancholic feelings about time passing.